German Plans for Central Europe - Gedeon, Magdolna (Great Theorists of Central European Integration, 2023)
German plans for Central Europe had already appeared in the 19th century. At the heart of the Mitteleuropa idea was the creation of an economic area under German leadership. In the literature, List is considered the father of the Mitteleuropa idea, the first systematic developer of the integration of Central and Eastern Europe under German leadership. His work ʻDas nationale System der politischen Ökonomie’ [The National System of Political Economy], in which he scientifically summarised and systematised his previous writings, was published in May 1841. In this work, List expressed his views in defense of political unity and national economy and against the teaching of Adam Smith’s school. List first advocated the realisation of a continental alliance against the English hegemony, and then, when the USA advanced, he believed that the English should also join the alliance. He wanted to promote the development of the economic region, by developing the railway and waterway network. Another famous German developer of the Mitteleuropa concepts is Friedrich Naumann. Within his work, the books and articles dealing with Mitteleuropa form a closed whole. These writings of his are closely related. Their time of origin also shows unity. Naumann elaborated his plan for Central Europe in his main work ‘Mitteleuropa’ published in November 1915. Central Europe was not to be a new state, but an alliance of existing states, the core of which would be the alliance between Germany and Austria-Hungary. It was to be a confederation and not a federal state.KEYWORDS: Mitteleuropa, Adam Smith, political economy, confederation, Oberstaat, Friedrich List, Friedrich Naumann